Analysis of the Export Growth Potential of Desiccated Coconut to Poland in 2022–2024 - Antasari Sibarani; Dwi Fauziansyah Moenardy (University of Merdeka Malang, 2025)
Indonesia, as the world’s second-largest coconut producer, holds significant potential for exporting desiccated coconut to international markets, particularly Poland. However, Indonesia’s market share in Poland remains behind the Philippines, which dominates desiccated coconut imports. The demand for this product in Poland continues to rise, driven by trends in healthy, plant-based food consumption and traditional food processing. This study aims to analyze the potential for increasing Indonesian desiccated coconut exports to Poland and to formulate appropriate strategies to optimize this market during 2022-2024. The research employs qualitative and quantitative methods, analyzing export data within the theoretical frameworks of John Stuart Mill’s international trade theory and Porter’s Diamond Model of competitive advantage. Findings indicate significant opportunities for export growth through improvements in product quality, diversification of value-added products, and strengthening distribution networks in Poland. Indonesia needs to overcome limitations in modern processing and adopt quality standards aligned with the European Union market. In conclusion, the development of innovative products and adaptive marketing strategies are crucial to enhancing the competitiveness of Indonesian desiccated coconut exports to Poland, supporting sustainable national economic growth.